Ageing, sport and physical activity participation in Scotland - Davison, R. C. Richard; Cowan, Daryl T. (Frontiers in Sports and Active Living, 2023)
Aim As sport and physical activity are vital to support extended health spans, this study aimed to analyse the current trends in sports participation and physical activity rates among individuals aged 65 years and older in Scotland. Data were compared with the Chief Medical Officer (CMO) guidelines and analysed the influence of key factors on participation rates. Methods The study used data from the Scottish Health Survey and the Scottish Household Survey (2019) to investigate self-reported participation in physical activity and sports across different age groups. Descriptive statistics and cross-tabulations were used to analyse the relationships between participation rates and influencing factors. Participation data for Parkrun events in Scotland were also analysed for the years 2008–2018. Results The study found a clear decline in sports participation with age, with a steep decline after the age of 65, particularly in women. The majority of participation among individuals aged 65+ was in walking, with a sport participation rate of only 31.2% when walking was excluded. Physical activity and sport participation was lower in women across all age ranges but particularly so in the 75+ age group. The most popular sporting activities in the older age group were keep fit/aerobics, swimming and golf. Additionally, the study found that social deprivation had a major impact on sports participation rates, with the most deprived households exhibiting the lowest participation levels irrespective of age. The prevalence of loneliness was lower among individuals who participated in sports or adhered to the CMO guidelines for moderate/vigorous physical activity and strength-building exercises. Discussion The findings of this study have implications for promoting physical activity and sports participation among older adults, particularly in deprived communities. This study highlights the importance of balance exercises within sport and the need for more targeted efforts to increase participation rates among older adults. The study also emphasizes the positive impact of sports participation on reducing loneliness among older adults. Overall, the findings suggest the need for ongoing efforts to promote physical activity and sports participation among older adults to improve their overall health and well-being.